2021
DOI: 10.3390/ijerph18041702
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Helping Informal Caregivers: A Systematic Review

Abstract: (1) Background: The physical and psychological consequences suffered by informal caregivers have been extensively studied. MHealth solutions appear to be an opportunity to help overcome the caregiver burden. The objective of this study was to evaluate available mobile applications for informal caregivers of people who are ill and to determine whether these mobile applications were developed considering the needs of caregiver users. (2) Methods: A systematic review was carried out using the MEDLINE, ProQuest, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
0
27
1
3
Order By: Relevance
“…Caregivers can access information to websites easily related to stroke [32], [33], post stroke caregiving, management problem for caregivers [33], and food information [31]. This result is supported by Sala-González et al [39] that their review found that this feature was also widely used in mobile application for caregivers.…”
Section: Discussionmentioning
confidence: 62%
“…Caregivers can access information to websites easily related to stroke [32], [33], post stroke caregiving, management problem for caregivers [33], and food information [31]. This result is supported by Sala-González et al [39] that their review found that this feature was also widely used in mobile application for caregivers.…”
Section: Discussionmentioning
confidence: 62%
“…In this context, it is necessary to become increasingly aware not only of the difficulties of caring for frail elderly but also of the consequences on the wellbeing of the caregivers, who should not lack social and professional support [58,59]. Furthermore, caregivers should be routinely included in educational health-oriented programs and strategies, jointly with patients and care professionals, in order to improve their knowledge and the quality of care [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of their needs is a priority, as defined by the World Health Organization [8]. Recent reviews showed that unmet needs of PIC have to be taken into account in a proactive approach of care planning from health care professionals, and that PIC are often not integrated enough in the health care system [9][10][11]. In 2011, the Belgian Health Care Knowledge Centre analyzed thirty forms of non-pharmaceutical therapy for people with dementia.…”
Section: Introductionmentioning
confidence: 99%